The Role of Digital Loyalty Program towards Customer Loyalty through a Measure of Satisfaction - Roymon Panjaitan (Bina Nusantara University, 2021)
The research aimed to explore the importance of loyalty programs to customer satisfaction and loyalty in digital business in Indonesia. The concept of theoretical development of the resource-advantage theory of competition and service-dominant logic was used for the development of research findings. Lazada, one of the e-commerce platforms, offered digital loyalty programs such as points store, loyalty store, e-coupon, e-newsletter, and flash sale. Thus data collection was distributed through an online questionnaire to Lazada customers, with a sample size of 384 respondents. Data testing with linear regression analysis was conducted to test the variables of the Lazada digital loyalty program on customer loyalty mediated customer satisfaction. The results shows that in digital loyalty program variables, the program features contribute positively directly and have the success of mediated customer satisfaction in the digital loyalty program. More products that offer customer-oriented technology feature innovation will increase customer loyalty amidst dynamic marketing capabilities in digital business innovation change, which gives impact to managers.